1994
DOI: 10.1002/gps.930090506
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among workers caring for the elderly

Abstract: SUMMARYThe GHQ-30 was used to assess psychological disturbance among staff working in four long-stay wards, four homes for the elderly mentally infirm, four elderly persons' homes and four private nursing homes. Rates of disturbance were consistent across all 16 units. Rates of CGHQ caseness were low, compared with published findings from a representative UK community sample. A strong relationship was demonstrated between staff psychological disturbance and aggression from residents over the last week. Disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 15 publications
0
39
1
Order By: Relevance
“…MacPherson et al (1994) came across the same contradictory results. In their study, a ward having high rates of long-term sickness proved to have the lowest rates of psychological disturbance.…”
Section: Discussionmentioning
confidence: 91%
“…MacPherson et al (1994) came across the same contradictory results. In their study, a ward having high rates of long-term sickness proved to have the lowest rates of psychological disturbance.…”
Section: Discussionmentioning
confidence: 91%
“…Over 80% of dementia suerers exhibit at least one or more troublesome behaviours (Swearer et al, 1988). The impact on carers has received deserved attention, and the association with stress is well recognized (Hinchclie et al, 1995;MacPherson et al, 1994;O'Connor et al, 1990). Of the many behavioural diculties faced by carers, aggression is one of the most dicult to cope with (Argyle et al, 1985).…”
mentioning
confidence: 97%
“…Previous studies suggested that job stressors among general teachers were high quantitative work load 7) , lack of support from supervisors 8) , and so on. Previous studies suggested that job stressors among staff engaged in nursing activity were physical work load 13) , conflict between staff and families of handicapped patients 10,13) , and lack of social support 11) . Teachers engaged in nursing activity in this study showed characteristics of job stressors both among general teachers and staff members engaged in nursing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that job stress among general teachers is associated with role overload 7) , conflict for parents of children 7) and lack of support from supervisors or coworkers 7,8) . There are also some studies of job stress among staff engaged in nursing activity [9][10][11][12][13] . Job stress among care workers in Japanese social welfare facilities has also been reported to be excessive compared to that in the general Japanese populations 9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation